Sequential C−H Borylation and N‐Demethylation of 1, 1′‐Biphenylamines: Alternative Route to Polycyclic BN‐Heteroarenes. Issue 22 (17th April 2019) - Zhang, Jianbo; Jung, Hoimin; Kim, Dongwook; Park, Sehoon; Chang, Sukbok
Abstract: Described herein is an unprecedented access to BN‐polyaromatic compounds from 1, 1′‐biphenylamines by sequential borane‐mediated C(sp 2 )−H borylation and intramolecular N‐demethylation. The conveniently in situ generated Piers' borane from a borinic acid reacts with a series of N, N ‐dimethyl‐1, 1′‐biphenyl‐2‐amines in the presence of PhSiH3 to afford six‐membered amine‐borane adducts bearing a C(sp 2 )−B bond at the C2′‐position. These species undergo an intramolecular N‐demethylation with a B(C6 F5 )3 catalyst to provide BN‐isosteres of polyaromatics. According to computational studies, a stepwise ionic pathway is suggested. Photophysical characters of the resultant BN‐heteroarenes shown them to be distinctive from those of all‐carbon analogues. Abstract : A two‐step borane‐mediated C−H borylation and N‐demethylation of biphenylamines has been developed to provide a range of new BN‐heteroarenes with distinct photophysical and structural properties. The unprecedented intramolecular N‐demethylation of borane‐amine intermediates was enabled by a B(C6 F5 )3 catalyst, albeit at high temperature. The procedure features transition‐metal‐free conditions to liberate environmentally benign byproducts (H2 and CH4 ) by a mechanistically intriguing ionic pathway.